2015
DOI: 10.1177/016146811511701204
|View full text |Cite
|
Sign up to set email alerts
|

Race and Belonging in School: How Anticipated and Experienced Belonging Affect Choice, Persistence, and Performance

Abstract: Background/Context A sense of belonging in school is a complex construct that relies heavily on students’ perceptions of the educational environment, especially their relationships with other students. Some research suggests that a sense of belonging in school is important to all students. However, we argue that the nature and meaning of belonging in school is different for students targeted by negative racial stereotypes—such as African American, Latino/a, Native American, and some Asian American students. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(77 citation statements)
references
References 73 publications
9
68
0
Order By: Relevance
“…Furthermore, students who majored in the Social Science discipline had significantly higher self-esteem and school belonging levels. This result supports the finding that students’ sense of self-esteem and school belonging is associated with their willingness to consider majoring in a discipline [ 70 ], yet it is contrary to the conclusion that there are no significant differences in the fields of self-esteem and school belonging among university students [ 71 ]. This result may be due to the type of university they are currently attending, which is well known for Social Science disciplines.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, students who majored in the Social Science discipline had significantly higher self-esteem and school belonging levels. This result supports the finding that students’ sense of self-esteem and school belonging is associated with their willingness to consider majoring in a discipline [ 70 ], yet it is contrary to the conclusion that there are no significant differences in the fields of self-esteem and school belonging among university students [ 71 ]. This result may be due to the type of university they are currently attending, which is well known for Social Science disciplines.…”
Section: Discussionsupporting
confidence: 83%
“…Students self-reported their gender (0 = male, 1 = female) and race/ethnicity, which we then coded to denote underrepresented racial minority (URM) group membership (0 = White, East Asian, and Southeast Asian students; 1 = Black, Hispanic, Indian Subcontinent, Native American, Mixed race, Middle Eastern, and Other race students). Because previous research has found mean-level differences in students’ belonging and evaluative concerns in STEM settings based on their gender and race (e.g., Murphy & Zirkel, 2015; Rudolph & Conley, 2005), we coded and controlled for these factors in our analyses so that we could observe the effect of faculty mindset above and beyond these potential group differences.…”
Section: Methodsmentioning
confidence: 99%
“…To assess students’ anticipated psychological vulnerability in the professor’s class, we measured their anticipated feelings of belonging using five items adapted from Murphy and Zirkel (2015; e.g., “How much would you feel that you ‘fit in’ during this class?”; α = .88). We also measured their anticipated evaluative concerns using five items adapted from Wout, Murphy, and Steele (2010; e.g., “How much would you worry that you might say the wrong thing in class?”; α = .90).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present research, we examine two aspects of inclusion: Sense of belonging and social identity threat. While sense of belonging captures more diffuse feelings of inclusion, social identity threat captures the extent to which students feel that their particular social groups are accepted in their college environments (Locks et al, 2008;Murphy & Zirkel, 2015). We consequently hypothesize that Hypothesis 3: Cross-race interactions will improve students' academic performance (i.e., college GPA), and they will do so by increasing students' feelings of inclusion in their universities (i.e., increase sense of belonging and decrease social identity threat).…”
Section: Consequences Of Cross-race Interactionsmentioning
confidence: 99%